An Analytical Study of Women Objectification in In Other Rooms, Other Wonders - Faheem Arshad (University of Chitral Journal of Linguistics and Literature, 2021)
The objectification of women is a communal problem in every developed and underdeveloped society of the world. Women make a major population of the world, and serve the society in multidimensional modes, but still they are considered feeble to men. The subject of women objectification has remained focus of various researchers globally. This research focused three short stories drawn from “In Other Rooms, Other Wonders” of Daniyal Mueenuddin to bring forward disparities and inequalities prevailing in patriarchal society of Pakistan. Additionally, it investigated the impact of these inequalities and injustices on downtrodden women of Pakistan. The objectification of women is such a discrimination that women are subjected to undergo in a patriarchal social set up. This study analyzes the objectification of women through the lenses of female characters selected from three short stories. This study uses theoretical frameworks of Martha Nussbaum and Rae Langton’s to draw outcomes for this study. Study findings exhibit that female characters undergo objectification and are treated as things by male in a male dominated strata of Pakistan.